Robotic Process Automation in Auditing: A Systematic Review - Wulandari, Wulandari; Nurfagfira, Uslifa; Desfana, Amanda; Manurung, Herlina (Jurnal Ilmiah Manajemen Kesatuan, 2023)
In the current era of digital transformation, Society 5.0 has significantly impacted various sectors, including accounting. Robotic Process Automation (RPA), an innovation arising from this transformation, enables the automation of business processes using software to execute repetitive tasks quickly and accurately. Public accountants, crucial players in ensuring compliance and financial report credibility, are not exempt from the influence of this transformation. The implementation of RPA in public accountant practices raises significant questions about the extent to which this technology can replace human roles in the audit process. While RPA can automate various routine audit tasks, including internal control testing, transaction processing, and financial data analysis, it challenges the traditional role of accountants in interpreting and making decisions based on broader business contexts. Despite the immense potential of RPA in enhancing audit efficiency and accuracy, several challenges need addressing, such as technology integration with existing systems, data security, and cultural changes among accounting professionals. The alignment of audit regulatory needs with RPA capabilities is also a crucial aspect to consider. This research refers to recent literature and case studies related to RPA implementation in public accounting, audit, and risk management contexts. The importance of this research lies in its contribution to understanding the impact of digital transformation, particularly RPA, on the public accountant profession.